Improved Performance in Mammalian Cell Perfusion Cultures by Growth Inhibition. Issue 2 (4th June 2018) - Wolf, Moritz K. F; Closet, Aurélie; Bzowska, Monika; Bielser, Jean‐Marc; Souquet, Jonathan; Broly, Hervé; Morbidelli, Massimo
Abstract : Mammalian cell perfusion cultures represent a promising alternative to the current fed‐batch technology for the production of various biopharmaceuticals. Long‐term operation at a fixed viable cell density (VCD) requires a viable culture and a constant removal of excessive cells. Product loss in the cell removing bleed stream deteriorates the process yield. In this study, the authors investigate the use of chemical and environmental growth inhibition on culture performance by either adding valeric acid (VA) to the production media or by reducing the culture temperature (33.0 °C) with respect to control conditions (36.5 °C, no VA). Low temperature significantly reduces cellular growth, thus, resulting in lower bleed rates accompanied by a reduced product loss of 11% compared to 26% under control conditions. Additionally, the cell specific productivity of the target protein improves and maintained stable leading to media savings per mass of product. VA shows initially an inhibitory effect on cellular growth. However, cells seemed to adapt to the presence of the inhibitor resulting in a recovery of the cellular growth. Cell cycle and Western blot analyses support the observed results. This work underlines the role of temperature as a key operating variable for the optimization of perfusion cultures. Abstract : Mammalian cell perfusion cultures represent a promising alternative to the current fed‐batch technology as production platform for a variety of therapeutic proteins. In this study, the authors demonstrate an approach to optimize perfusion cultures by applying external growth inhibition, e.g., environmental growth inhibition (EGI) and chemical growth inhibition (CGI), leading to improved process yield and stable cell specific productivity of the target protein. This work demonstrates the importance of external levers, especially temperature, for controlling cell growth and process optimization in mammalian cell perfusion cultures.